2019
DOI: 10.1186/s12879-019-4554-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of extended-spectrum β-lactamase (ESBLs) – producing Escherichia coli from minced meat of cattle and swab samples and hygienic status of meat retailer shops in Jimma town, Southwest Ethiopia

Abstract: BackgroundThe impact of animals sources of food as a possible reservoir for extended-spectrum β-lactamase (ESBL) - Producing E. coli, and the dissemination of such strains into the food production chain need to be assessed. This study was aimed to assess the presence and antimicrobial susceptibility patterns of ESBLs - producing E. coli isolates from minced meat and environmental swab samples at meat retailer shops of Jimma town, Southwest Ethiopia.MethodologyA cross-sectional descriptive study was conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
(16 reference statements)
3
23
2
Order By: Relevance
“…Accordingly, a total of 98 (76.6%) E. coli and E. coli O157: H7 isolates were resistant to two or more classes of antibiotics. The prevalence of multi-drug resistant isolates was also reported in previous studies in Ethiopia [8,14,19,20,25,33], in which about (33.2-100%) of isolates were showed multidrug resistance. The occurrence of multidrug resistance may be linked with indiscriminate utilization of antimicrobial agents or genetic mutation, which was not elucidate with the present study methodology.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Accordingly, a total of 98 (76.6%) E. coli and E. coli O157: H7 isolates were resistant to two or more classes of antibiotics. The prevalence of multi-drug resistant isolates was also reported in previous studies in Ethiopia [8,14,19,20,25,33], in which about (33.2-100%) of isolates were showed multidrug resistance. The occurrence of multidrug resistance may be linked with indiscriminate utilization of antimicrobial agents or genetic mutation, which was not elucidate with the present study methodology.…”
Section: Resultssupporting
confidence: 72%
“…In this study, third generation cephalosporin (cefotaxime, ceftriaxone and cefotaxime), gentamycin, cipro oxacin, kanamycin, streptomycin and chloramphenicol showed best activities against our isolates. The best e cacies of the above antibiotics were also reported in previous study ndings in Ethiopia with different resistance rate [14,15,17,18,25,33]. In contrast, higher resistance was observed against erythromycin and ampicillin, followed by tetracycline, co-trimoxazole and amoxicillin -clavulanic acid.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Studies concerning ESBL-PE among human began in 2005 in Ethiopia [ 21 ]. Despite study trends increases, none of them provides a comprehensive picture of the epidemiology of ESBL-PE conducted in the different regions of the country [ 6 , 7 , 12 , 21 23 , 26 , 27 , 29 , 33 , 40 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest prevalence (16 %) of ESBL-producing Enterobacteriaceae was reported in studies conducted in Gondar town [54] and the highest prevalence (79 %) was reported in Addis Ababa [55]. Most of the studies were from Addis Ababa [55][56][57][58][59] and from the Oromia region [57,[60][61][62] (Table 1).…”
Section: Description Of Included Studiesmentioning
confidence: 99%